Why is Prior Consultation Not Yet an Effective Tool for Conflict Resolution? The Case of Peru - Almut Schilling-Vacaflor; Riccarda Flemmer (German Institute of Global and Area Studies (GIGA), 2013)
Prior consultation is an increasingly accepted instrument internationally for guaranteeing the rights of indigenous peoples. Conceived of theoretically as a means for conflict resolution, in practice it lies at the heart of social conflicts all over Latin America. Using concepts from the contentious politics approach, we take a closer look at Peru - where indigenous mobilizations would lead to the only Latin American consultation law enacted to date. We also critically analyze the content and formulation of its regulating norm. We argue that this new legislation will not help to turn such consultations into a tool for conflict resolution as long as the normative framework itself is contested and the necessary basic conditions are not in place. The most important conditions that we identify for implementing effective prior consultation are impartial state institutions capable of justly balancing the diverse interests at stake, measures that reduce power asymmetries within consultations, and joint decision-making processes with binding agreements.
Keywords: 300; prior consultation; Peru; conflict resolution; contentious politics; indigenous peoples; extractive industries